2017
DOI: 10.3892/mmr.2017.7611
|View full text |Cite
|
Sign up to set email alerts
|

Mediating macrophage immunity with wogonin in mice with vascular inflammation

Abstract: Vascular inflammation may induce a number of diseases, including organ damage or failure, heart attack and stroke. The present study aimed to investigate the use of wogonin, a compound extracted from herbs, to mediate inflammatory reactions in vascular inflammation. Wogonin was loaded in a well‑characterized polymeric biomaterial carrier. In mice with streptozotocin‑induced vascular inflammation, wogonin treatment regulated the production of inflammatory cytokines, including interleukin‑6, tumor necrosis facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
(59 reference statements)
0
12
0
Order By: Relevance
“…Wogonin is a natural flavonoid component extracted from the dried root of Scutellaria baicalensis . Various studies showed its direct anti-inflammatory effects and immunoregulation on immune cells [ 37 ]. Interestingly, Wogonin was proved as a particular therapeutic adjuvant for anti-inflammation [ 14 ], which inspired our explorations of the potential role of Wogonin in MSC medication on IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Wogonin is a natural flavonoid component extracted from the dried root of Scutellaria baicalensis . Various studies showed its direct anti-inflammatory effects and immunoregulation on immune cells [ 37 ]. Interestingly, Wogonin was proved as a particular therapeutic adjuvant for anti-inflammation [ 14 ], which inspired our explorations of the potential role of Wogonin in MSC medication on IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al, 2020 , Li et al, 2017 , Li et al, 2017 , Li et al, 2017 , Wang et al, 2017 , Wang et al, 2016 , Wang et al, 2017 , Wang et al, 2016 , Xu and Zhang, 2020 , You et al, 2020 .…”
Section: Uncited Referencesmentioning
confidence: 99%
“…Wogonin treatment also regulated the production of inflammatory cytokines in mice with streptozotocin-induced vascular inflammation (Wang J et al. 2017).…”
Section: Pharmacological Activities Of Extracts and Major Compoundsmentioning
confidence: 99%